Estimation of Antiurolithic Activity of Gokhru and Comestible in Experimental Urolithic Rats - chavva, Pavitra; myreddy, Jayasree; srikanth, Sharadha; chidrawar, Vijay R.; rao, Uma Maheshwar (Asian Journal of Pharmaceutical Research and Development, 2013)
Tribulus terrestris grows widely in the the warmer region of India including west Rajasthan and Gujarat. It contains many active constituents like flavonoids, steroids, terpinoids, phenols, alkaloids and tannins. It is reported to have hepatoprotective, anti-microbial, anti-inflammatory, antihypertensive, diuretic, and urinary anti-infectives. The present study was aimed at evaluating the hydroalcoholic extract of fruits of Tribulus terrestris (Gokhru, HAEG), at dose of 50mg/kg and also along with the comestible for anti-urolithic activity. Anti-urolithic activity of the the hydroalcoholic extract of Gokhru at dose of 50mg/kg along with comestible was evaluated by ethylene glycol (0.75% W/V) induced hyperoxalurea in group II, III, IV and V animals. Group I was taken as normal, group II was taken as control, group III as standard group, group IV and V received HAEG and HAEG along with diet. BUN and creatinine were estimated in serum. Oxalate, calcium, phosphate, magnesium and uric acid were estimated in urine. Histopathological studies were also done for all the groups.The hydroalcoholic extract of Gokhru (HAEG) at dose of 50mg/kg along with comestible was evaluated by ethylene glycol induced hyperoxalurea in rats. Interpretation of the results was done after subjecting the data obtained from various studies to statistical analysis which included one way ANOVA followed by post test (Tukey’s). The results suggest that the group that was treated with HAEG along with comestible had shown better protective activity when compared to alone HAEG.